2021
DOI: 10.1111/ecc.13415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of the clinical Nurse Specialist in cancer care: an integrative literature review

Abstract: There has been a growing international interest in extending nursing practice beyond the level acquired at initial registration (East et al., 2015) to advanced nursing roles. The role of the nurse has steadily evolved over the previous two decades due to influencing factors such as developments in healthcare delivery, financial restraints and increasing service user expectations (Furlong & Smith, 2005). One commonly identified category of Advanced Practice Nursing is the Clinical Nurse Specialist (CNS) role (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 27 publications
3
58
0
4
Order By: Relevance
“…Key worker’s expertise and experience were at the core of maintaining all types of continuity. Similar to others, our work shows that this continuity, that involved emotional, educational and practical support, was at its best when experienced, clinical nurse specialists were performing this role (Kerr et al, 2021 ). Coherent, connected and consistent care was delivered by these experts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Key worker’s expertise and experience were at the core of maintaining all types of continuity. Similar to others, our work shows that this continuity, that involved emotional, educational and practical support, was at its best when experienced, clinical nurse specialists were performing this role (Kerr et al, 2021 ). Coherent, connected and consistent care was delivered by these experts.…”
Section: Discussionsupporting
confidence: 85%
“…Often this role is fulfilled by skilled nurses, usually a clinical nurse specialist, acting as a type of “broker”, to provide instrumental and relational functions and processes to support patients, and families, quickly identifying emerging issues and improving the overall patient experience (National Cancer Action Team, 2012 ). The positive contributions to adult cancer care made by clinical nurse specialists and their role as key workers, across the range of diseases, is well documented, revealing their responsibilities to be multifaceted and diverse (Kerr et al, 2021 ). The key worker role has been implemented in children’s cancer care, but how it is perceived by other staff members, patients and families, has so far not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Swedish study found that the implementation of a new oncology nursing role led to improvements in patients' perceptions of health‐related information, supportive care resources and care coordination of care (Westman et al, 2019 ). In addition, a recent review showed that studies from several countries other than the United Kingdom, including Ireland, the Netherlands, Australia, New Zealand and South Korea, found that the CNS role was important in improving patient satisfaction, symptom management, meeting information needs and improving subsequent care outcomes (Kerr et al, 2021 ). Our findings are therefore consistent and suggest that it is the presence of a CNS that is important in leading to patients' reports of better experiences.…”
Section: Discussionmentioning
confidence: 99%
“…This review also highlights that poor acknowledgement by senior managers of the CNS role and unsustainable workload also fuel burn-out. Health service personnel outside the immediate MDT in which the specialist nurse sits, have a poor understanding of the complexity and range of the CNS role36 37 despite growing evidence on the clinical value of CNSs and the positive impact on patient care 38–42. Workload across IBD-CNSs has been shown to exceed recommended guidelines, with 63% of participants in one study reporting a caseload above the recommended level, and 84% doing unpaid overtime to manage this3; the consequence is that the opportunities for PA may diminish.…”
Section: Discussionmentioning
confidence: 99%